Repeat Closed-Head Injury in Male Rats Impairs Attention but Causes Heterogeneous Outcomes in Multiple Measures of Impulsivity and Glial Pathology - Vonder Haar, Cole; Wampler, Sarah K.; Bhatia, Henna S.; Ozga, Jenny E.; Toegel, Cory; Lake, Anastasios D.; Iames, Christopher W.; Cabral, Caitlyn E.; Martens, Kris M. (Frontiers in Behavioral Neuroscience, 2022)
Repetitive mild traumatic brain injury, or concussion, can lead to the development of long-term psychiatric impairments. However, modeling these deficits is challenging in animal models and necessitates sophisticated behavioral approaches. The current set of studies were designed to evaluate whether a rubberized versus metal impact tip would cause functional deficits, the number of injuries required to generate such deficits, and whether different psychiatric domains would be affected. Across two studies, male rats were trained in either the 5-choice serial reaction time task (5CSRT; Experiment 1) to assess attention and motor impulsivity or concurrently on the 5CSRT and the delay discounting task (Experiment 2) to also assess choice impulsivity. After behavior was stable, brain injuries were delivered with the Closed-head Injury Model of Engineered Rotational Acceleration (CHIMERA) either once per week or twice per week (Experiment 1) or just once per week (Experiment 2). Astrocyte and microglia pathology was also assayed in relevant regions of interest. CHIMERA injury caused attentional deficits across both experiments, but only increased motor impulsivity in Experiment 1. Surprisingly, choice impulsivity was actually reduced on the Delay Discounting Task after repeat injuries. However, subsequent analyses suggested potential visual issues which could alter interpretation of these and attentional data. Subtle changes in glial pathology immediately after the injury (Experiment 1) were attenuated after 4 weeks recovery (Experiment 2). Given the heterogenous findings between experiments, additional research is needed to determine the root causes of psychiatric disturbances which may arise as a results of repeated brain injuries.